On the Pressure Generated by Thermite Reactions Using Stress‐Altered Aluminum Particles. Issue 1 (30th November 2020) - Williams, Alan; Shancita, Islam; Altman, Igor; Tamura, Nobumichi; Pantoya, Michelle L.
Abstract: This study examines pressure build‐up and decay in thermites upon impact ignition and interprets reactivity based on the holistic pressure history. The thermite is a mixture of aluminum (Al) combined with bismuth trioxide (Bi2 O3 ) powder. Four different Al particles sizes were examined that ranged from 100 nm to 18.5 μm mean diameter and for each size, two different Al powder treatments were examined: stress‐altered compared to untreated, as‐received Al powder. Stress‐altered Al powders have been shown to be more reactive, such that the stress‐altered Al powder thermites offer a metric for analyzing thermite reactivity in terms of pressure development compared to untreated Al powder. In a binary thermite system, multiple phase changes and interface chemistry influence the transient pressure response during reaction. Results reveal three key pressure metrics that need consideration specifically for thermite combustion: (1) delay time to peak pressure, (2) peak pressure, and (3) decay after peak pressure. Our experiments show that a lower peak pressure corresponds with higher thermite reactivity because aluminum consumption of oxygen generated by decomposing solid oxidizer reduces the peak pressure. Faster rates of reaction consume oxygen at higher rates such that pressure development becomes more limited than less reactive thermites and the result is a lower peak pressure. This conclusion is opposite of traditional studies using metal fuels with a gaseous environment that typically show higher peak pressures correspond with greater reactivity. Abstract :